The Effect of EM4 Addition in the Biofilter Tanks to Reduce the TSS and Ammonia in the Palm Oil Industry Liquid Waste - Aji Santoso; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractPalm oil liquid waste is rich in TSS and ammonia and thus need to be processed before being flown to environment. A study aims to reduce the TSS and ammonia in that waste by using a biofilter that was added with EM4 has been conducted in March-April 2019. There were 3 treatments applied, namely the addition of 12 ml, 15 ml and 18 ml EM4 in the anaerob and aerob tanks, 3 replications. The waste was settled for 3 days in the anaerob and 3 days in the aerob tanks. The treated waste was then tested for TSS and ammonia concentrations. The treated waste was also used for rearing Pangasius sutchi seedlings. Result shown that after being treated using the EM4 enriched biofilter the TSS reduced into60-71.66 mg/L and ammonia was 2.5047-5.3624 mg/L. The survival Pangasius sutchi seedlings reared in the treated waste was 66.66-93.33%. The best treatment to reduce the TSS was the addition of 15 ml EM4 and the effectiveness was 60 mg/L while that of the ammonia was 2.5047 mg/L. It can be concluded thatthe addition of EM4 to the biofilter tanks was able to reduce the TSS and ammonia in the palm oil industrial liquid waste. Keywords: Waste water, Effective Microorganism-4, Pangasius sutchi, Biofilter System.